Microencapsulation of probiotic Saccharomyces cerevisiae var. boulardii with different wall materials by spray drying - Arslan, Sultan; Erbas, Mustafa; Tontul, Ismail; Topuz, Ayhan (Elsevier Science Bv, 2015)
Saccharomyces cerevisiae var. boulardii have probiotic properties which are beneficial for human health. It has been commonly used as a drug against gastrointestinal disorders. Saccharomyces boulardii has been used in some food formulations in recent years, due to its probiotic properties. However, it is not sufficiently stable for food processing and gastrointestinal systems. In this study, S. boulardii was microencapsulated with six different wall materials (gelatin, whey protein concentrate, modified starch, maltodextrin, pea protein isolate and gum Arabic) and spray dried using two different inlet temperatures (80 degrees C and 125 degrees C). The highest product yield was obtained with whey protein concentrate and gum Arabic. Survivability of the S. boulardii did not change with the wall materials, but it increased at the lower drying temperature. Survivability in a simulated gastric solution test at different pH levels and durations showed that gum Arabic is the best wall material followed by gelatin and pea protein. The microcapsules produced at the higher drying temperature (125 degrees C) showed, a higher resistance to the gastric solution than those of the lower drying temperature (80 degrees C). In addition, survivability was decreased by increasing exposure time to the simulated gastric solution. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Saccharomyces boulardii; Probiotic yeast; Spray drying; Microencapsulation; Wall materials